1997
DOI: 10.1128/jvi.71.5.3666-3676.1997
|View full text |Cite
|
Sign up to set email alerts
|

Complete nucleotide sequence of simian endogenous type D retrovirus with intact genome organization: evidence for ancestry to simian retrovirus and baboon endogenous virus

Abstract: A complete endogenous type D viral genome has been isolated from a baboon genomic library. The provirus, simian endogenous retrovirus (SERV), is 8,393 nucleotides long and contains two long terminal repeats and complete genes for gag, pro, pol, and env. The primer binding site is complementary to tRNA 3 Lys , like in lentiviruses. The env GP70 protein is highly homologous to that of baboon endogenous virus (BaEV). PCR analysis of primate DNA showed that related proviral sequences are present in Old World monke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 45 publications
(68 reference statements)
2
44
0
Order By: Relevance
“…Studies on col‐SERVs lag far behind those on cer‐SERVs (particularly macaque SERVs), although a few studies have identified SERVs in Colobinae monkeys (Sommerfelt et al, ; Todaro et al, ). One reason for the apparent lack of interest in col‐SERVs is that an early hybridization‐based screening failed to identify SERVs in Colobus guereza (van der Kuyl, Mang, Dekker, & Goudsmit, ), which suggested that SERVs were integrated after the divergence between Cercopithecinae and Colobinae monkeys. Another reason is that the genomic resources of Cercopithecinae monkeys including draft genome sequences are better established than those of Colobinae monkeys, partly because Cercopithecinae monkeys have been preferentially used for biomedical research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on col‐SERVs lag far behind those on cer‐SERVs (particularly macaque SERVs), although a few studies have identified SERVs in Colobinae monkeys (Sommerfelt et al, ; Todaro et al, ). One reason for the apparent lack of interest in col‐SERVs is that an early hybridization‐based screening failed to identify SERVs in Colobus guereza (van der Kuyl, Mang, Dekker, & Goudsmit, ), which suggested that SERVs were integrated after the divergence between Cercopithecinae and Colobinae monkeys. Another reason is that the genomic resources of Cercopithecinae monkeys including draft genome sequences are better established than those of Colobinae monkeys, partly because Cercopithecinae monkeys have been preferentially used for biomedical research.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic sequences highly homologous to SRV genes were first identified in a baboon ( Papio cynocephalus ) (van der Kuyl et al, ) and termed as simian endogenous retroviruses (SERVs). Although the sequences isolated in this study contained frameshift mutations, the basic genomic architecture of SRVs was preserved in SERVs, suggesting that SERVs are fossils of ancient SRVs.…”
Section: Introductionmentioning
confidence: 99%
“…In simian immunodeficiency virus, the virus harbored by sabaeus monkeys is a recombinant between African green monkey and sooty mangabey simian immunodeficiency viruses (12). Also, BaEV itself is a recombinant between C-type (PcEV) and D-type (SERV) primate retroviruses (17,27).…”
Section: Discussionmentioning
confidence: 99%
“…The last common ancestor of the Cercopithicinae supposedly lived at least 9 million years ago, indicating that exogenous BaEV was spreading in Africa after that time. BaEV is a recombinant retrovirus, containing type C gag and pol genes and a type D env gene, which probably arose by recombination of two primate viruses (simian endogenous retrovirus [SERV] and Papio cynocephalus endogenous virus [PcEV]), whose genomes are also present in monkey genomic DNA (17,27). RD-114 has the same mosaic genomic structure as BaEV.…”
mentioning
confidence: 99%
“…Two complete endogenous retroviral sequences, those of baboon endogenous virus (BaEV) (15) and simian endogenous retrovirus (SERV) (39), have been isolated from the genome of the baboon (Papio cynocephalus). Originally, BaEV was isolated from baboon tissue by cocultivation with permissive cell lines (3,34).…”
mentioning
confidence: 99%